Socio-economic Impacts of Emigration on Developing Countries – A Focus on Nepal and South Asia - Panthi, Sushil Kumar (Journal of Rapti Babai Campus, 2026)
Emigration is the process of transfer of persons from their residence nation to other countries for diverse objectives, temporarily or permanently. In the recent decade, emigration has emerged as one of the most powerful worldwide social and economic processes affecting development, labor markets, demographic patterns and family systems. This study explores the social economic implications of emigration on Nepal and South Asian countries where international level migration has become a vital development strategy for millions of people. This research deals with three important questions: What are the primary causes of emigration from Nepal and South Asia? How do remittances affect poverty reduction, education and healthcare in origin countries? What are the long term social costs including family separation, gender role shifts and skilled labor loss? Using a mixed methods approach incorporating secondary quantitative data from government sources. World bank data and case studies from Nepali migration corridors, this study reveals that while remittances deliver fast economic assistance and poverty reduction the departure of competent workers and prime age laborers produces major development challenges. The research presents tangible advice for governments to support inclusive, equitable and sustainable migration strategies, ensuring that migration becomes a driver of global development.